Design and application of depth control methods for autonomous underwater profilers in challenging marine environments - Isabel P. Morales-Aragón; Jaime Giménez-Gallego; Javier Gilabert; Roque Torres-Sánchez; Fulgencio Soto-Valles (Results in Engineering)
Coastal lagoons, such as the Mar Menor, have suffered significant environmental crises that have adversely affected tourism, leisure, and fishing activities, while also decreasing property values in the area. To address the challenges of restoring these ecosystems, the development of automated methods for continuous monitoring of various parameters at different depths and locations is being promoted. In this context, a lightweight, autonomous, submersible profiler with depth control capability was designed for monitoring the stratifications in shallow waters like the Mar Menor. This study presents two depth control methodologies for the profiler: a system based on thrusters, and another based on a variable ballast system, along with the challenges encountered during real-world tests of each methodology. The first methodology uses a simple PID control algorithm to manage depth via thrusters, suitable for marine environments where fouling is minimal. This system resulted in a mean absolute depth error of 5.6 cm and an autonomy of 127 days. The second methodology, based on a variable ballast system, is effective even in environments with significant fouling. It employs a cascaded control structure with a rule-based dynamic operating point, achieving a mean absolute depth error of 5.7 cm and an autonomy of 48 days in locations of the Mar Menor.